Analisis Pengambilan Keputusan Rasionalitas Pada Kebijakan Presiden Dibawah Umur 40 Tahun Yang diTetapkan Oleh Mahkamah Konstitusi (MK) - Naufal Syaraful Wafa’; Ilhamsyah gema fitrah; M. Noer Falaq Al Amin (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
A thorough examination of the temporal dynamics of politics is undertaken in this study. Just days before the last deadline for presidential and vice presidential candidates to register, the public was stunned by the contentious judgement of the Constitutional Court (MK). This research seeks to utilise a rational decision-making framework to understand the rationale behind the Constitutional Court's (MK) ruling on the eligibility of presidential and vice presidential candidates under the age of 40, as outlined in article 90/PUU-XXI/2023. This ruling is a continuation of the previous article, specifically Article 169 letter q of Law Number 7 of 2017 concerning Elections, which established this age limit. In addition to original data collected from applicable statutes, journals, and other sources, this study employs a literature review methodology. this study delves into the relationship between the determination process and article 90/PUU-XXI/2023. The participants in this research demonstrated a comprehension of rational choice principles and the process of choosing presidential and vice presidential candidates, according to the findings. As well as showing that the decisions decided are subjective and irrational because they focus on actors because actors are considered as humans with goals, which means they perform certain actions and goals to achieve their goals.